Evaluation of Elemental Distributions in Wild-Caught and Farmed Pangasius sp. Using Pattern Recognition Techniques. Issue 7 (2nd July 2016) - Low, Kah Hin; Idris, Nor Shahirul Umirah; Md. Zain, Sharifuddin; Kamaruddin, Ahmad Firdaus; Md. Salleh, Kaharudin
Abstract : The concentrations of Na, Mg, K, Ca, Cr, Fe, Ni, Cu, Zn, As, Se, and Pb in various tissues of Pangasius sp. were determined using microwave-assisted digestion/inductively coupled plasma–mass spectrometry. The clustering tendency related to elemental patterns associated with tissue variants and fish habitats were explored using hierarchical cluster analysis and principal component analysis. The results revealed that the general elemental accumulation pattern was strongly dependent on the type of tissue, whereas latent deviations within particular tissue samples can be linked to the natural variability between wild-caught and farmed fish. The inherent elemental patterns allowed us to differentiate between those wild-caught and farmed fish through linear discrimination analysis with 100% precision. In terms of food safety, the elemental concentrations in edible muscle were found to be far below the legal limits, as the associated health risks at the 90th percentile were well within tolerable regions, although wild-caught fish were found to pose a higher risk.